Hubungan Persepsi tentang Pembelajaran Ekonomi dan Kemampuan Awal dengan Hasil Belajar Mata Pelajaran Ekonomi - Afri Nurhayati; Z Mawardi Effendi (Jurnal Ecogen, 2021)
This study aims to determine the relationship: 1) Students 'Perceptions of Economic Learning and Initial Ability and Learning Outcomes, 2) Students' Perceptions of Economic Learning and Learning Outcomes, 3) Initial Ability and Learning Outcomes. The research was conducted on students at SMA Negeri 7 Padang. This type of research is a quantitative study with a correlational method. The sampling technique used in this study was proportional random sampling with a sample of 143 students. The data used are secondary and primary data. Data collection techniques in the form of questionnaires and tests. Data analysis used descriptive and inductive analysis using normality test, linearity test, hypothesis test using person correlation test and determination coefficient test, where analysis was performed using SPSS Version 22. The results showed that 1) students' perceptions of economic learning and initial abilities had a moderate relationship with learning outcomes seen from the simultaneous contribution of 0.597 with sig 0.000 ˂ 0.05. 2) students' perceptions about economic learning and learning outcomes have a very strong relationship with the Pearson Correlation value 0.819 with Sig 0.000 ˂ 0.05. 3) initial ability with learning outcomes has a moderate relationship with the Pearson correlation value of 0.596 with sig 0.000 ˂ 0.05.Keywords : students perceptions of learning economics, initial abilities, learning outcomes